Magnetic-control multifunctional acoustic metasurface for reflected wave manipulation at deep subwavelength scale - Xing Chen; Peng Liu; Zewei Hou; Yongmao Pei (Scientific Reports, 2017)
Abstract Acoustic metasurfaces, exhibiting superior performance with subwavelength thickness, are ideal alternatives for functionalities such as wavefront modulation and acoustic energy trapping, etc. However, most of the reported acoustic metasurfaces were passive. Here a magnetically tuned mechanism is reported for membrane-type acoustic metamaterials. Harnessing the geometric nonlinearity of membrane structures, the transmission spectrum is both theoretically and experimentally tuned over broadband by an external static magnetic force. Simultaneously, the phase profiles can be readily tailored by the magnetic stimulus. Further, a magnetic-control multifunctional metasurface is proposed for low-frequency wave manipulation. By switching the magnetic force distribution, multi extraordinary phenomena, such as acoustic wave redirecting, focusing, bending, etc., are realized without changing the physical structure. Besides, it is demonstrated the proposed metasurface, at deep subwavelength scale (~1/85λ), supports anomalous reflected wave manipulation over a wide band. These results open up new degrees of freedom to steer acoustic wave and pave a way for designing active acoustic devices.